Pengaruh e-Recruitment dan Reputasi Perusahaan terhadap Minat Melamar Pekerjaan pada Generasi Z - Anida Shabrina Haq; Kartika Sukmawati (Soratekno Publisher, 2025)
This study aims to analyze the effect of e-recruitment and company reputation on interest in applying for jobs in Generation Z, both partially and simultaneously. The method used is descriptive quantitative with primary data collected through an online questionnaire to 100 respondents drawn using a purposive sampling technique. Data analysis tools used IBM SPSS Statistics 26 through validity and reliability tests, classical assumption tests, and multiple linear regression tests and hypothesis testing (t test, f test, and coefficient of determination). The results showed that e-recruitment and company reputation have a positive and significant effect on the interest in applying for jobs in Generation Z, both partially and simultaneously. This finding emphasizes the importance of considering recruitment factors or schemes and company reputation as one of the strategies to improve the quality of human resources in a company.